Perturbing the community grammar: Individual differences and community-level constraints on sociolinguistic variation. Issue 1 (11th February 2019) - MacKenzie, Laurel
Abstract : The traditional focus of variationist sociolinguistic research is the patterning of language variation at the level of the community, which individual language users are said to learn and reproduce (Labov 1972 ; 2012 ). In this paper, I observe that, although members of a speech community may all have learned the same grammar of a sociolinguistic variable, they may nonetheless produce that variable in ways which obscure this. This "perturbation, " I argue, is epiphenomenal, stemming from at least two possible sources: individual differences in mental representations, and individual differences in speech production planning. Moreover, I demonstrate that these differences are not only inter-individual; they can also be intra-individual, such that speakers may undergo age-grading which disrupts their patterning of a variable from how they previously produced it. I ask whether these individual differences may give rise to changes in constraints in the same way that individual differences can lead to sound change. The paper concludes with a call for more research that integrates sociolinguistic, formal, and psycholinguistic approaches to the study of language variation and change.